PENGARUH KONTEN MUSYAWARAH DI YOUTUBE @NAJWA SHIHAB TERHADAP PERSEPSI SUBSCRIBER PADA ISU-ISU TERKINI - PUTRI SURYA NINGSIH BR SINAGA; RISWANDI RISWANDI (SCIENTIA JOURNAL, 2026)
This study aims to determine the influence of Musyawarah content on the @NajwaShihab YouTube channel toward subscribers' perceptions of current issues. The research employs a quantitative approach with a survey method. Data collection was conducted by distributing questionnaires to 114 respondents who are subscribers of the @NajwaShihab YouTube channel. The data were analyzed using SPSS version 25 software through validity tests, reliability tests, classical assumption tests, and simple linear regression analysis. The results of the validity test showed that all statement items were valid, while the reliability test indicated that the instruments were reliable. The normality test results showed an Asymp. Sig. value of 0.083 (> 0.05), meaning the data are normally distributed, and the heteroscedasticity test result was 0.814 (> 0.05), indicating no heteroscedasticity symptoms occurred. The simple linear regression analysis results demonstrate that Musyawarah content has a positive and significant influence on subscriber perceptions, with a regression coefficient value of 0.647 and a significance value of 0.000 (< 0.05). The regression equation obtained is $Y = 4.508 + 0.647X$. The coefficient of determination ($R^2$) result of 0.862 or 86.2% indicates that the subscriber perception variable can be explained by the Musyawarah content variable, while the remaining 13.8% is influenced by other factors outside this study. Consequently, the hypothesis stating that there is an influence of Musyawarah content on the @NajwaShihab YouTube channel toward subscribers' perceptions of current issues is accepted. Keywords: Musyawarah Content, YouTube, Subscriber Perception, Current Issues.